Environmentally conscious behavior among Malaysians consumers: an empirical analysis - Zuraidah Ramly,; Nor Hashima Hashim,; Wan Kalthom Yahya,; Siti Aishah Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper aims to investigate the influence of demographic and psychographicv variables on environmentally conscious cosumer behavior (ECCB)v in the context of Malaysian consumers. A survey was developed and administered. generating a total sample of 319 respondents across the country. The preliminary results indicated that all of the variables examin ed were significantly correlated to ECCB, expert for income. Later the analysis from the regression highlighted that only age, gender and perceived consumer effectiveness (PCE)were significant predictors to ECCB. The findings confirmed that, in terms of psychographic variables, PCE has been proven to be more accurate and significant determinant than environmental concern (EC) for segmenting and explaining different segments and characteristics of pro-environmental behavior .These findings may assist Malaysian policy makers in formulating actionable decisions related to environmental education and protection.The finding also allows marketers to use marketing and awareness-raising campaigns to encourage consumers to choose environmental friendly products.